1999
DOI: 10.1161/01.hyp.34.1.4
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Linkage Between Essential Hypertension and a Putative Locus on Human Chromosome 17

Abstract: Abstract-Several clinical and animal studies indicate that essential hypertension is inherited as a multifactorial trait with a significant genetic and environmental component. In the stroke-prone spontaneously hypertensive rat model, investigators have found evidence for linkage to blood pressure regulatory genes (quantitative trait loci) on rat chromosomes 2, 10, and X. In 1 human study of French and UK sib pairs, evidence for linkage has been reported to human chromosome 17q, the syntenic region of the rat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
62
0

Year Published

2001
2001
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(65 citation statements)
references
References 20 publications
(22 reference statements)
3
62
0
Order By: Relevance
“…A locus for essential hypertension has been reported on chromosome 17 in several chromosomal microsatellite scans, [1][2][3] as had been noted for the equivalent region in the genome of genetically hypertensive rats. 4,5 Recently, interest has focused on WNK4 (chromosome 17q21.2), which encodes a serine-threonine kinase with no lysine (K), but instead has a cysteine at a key position in the active site.…”
mentioning
confidence: 66%
“…A locus for essential hypertension has been reported on chromosome 17 in several chromosomal microsatellite scans, [1][2][3] as had been noted for the equivalent region in the genome of genetically hypertensive rats. 4,5 Recently, interest has focused on WNK4 (chromosome 17q21.2), which encodes a serine-threonine kinase with no lysine (K), but instead has a cysteine at a key position in the active site.…”
mentioning
confidence: 66%
“…15 Comparative genome analysis of rat, mouse, and human can be used to identify regions of the human genome likely to harbor genes involved in blood pressure regulation. 7,16 Julier et al 17 and Baima et al 18 provided first successful examples of comparative mapping in which a region involved in blood pressure regulation on rat chromosome 10 indicated a susceptibility locus for human hypertension on human chromosome 17q.…”
mentioning
confidence: 99%
“…Since the identification of QTLs contributing to blood pressure variation in rat chromosome 10 in several experimental models of hypertension, 14,15 several studies have reported evidence of linkage of hypertension to the 17q syntenic region in humans. 6,10,16 Although the ACE gene, encoding the angiotensin I-converting enzyme, is located within the linked chromosomal region in rats, the human homologue is situated 18 cM proximal to the blood pressure QTL and, therefore, does not seem to overlap with the candidate region. 16 Close examination of the QTL interval at 17q12-21 discloses no obvious functional candidate genes for blood pressure variation.…”
Section: Discussionmentioning
confidence: 99%